Oxide solid electrolyte material and preparation method thereof, diaphragm-free lithium ion battery, lithium ion battery and electric equipment
By setting a lithium silicate layer on the surface of the oxide solid electrolyte particles, the problem of LLZO material reacting with air during nanoification is solved, and the combination of high ionic conductivity and air stability is achieved, improving the performance and safety of the battery.
Patent Information
- Application Number
- CN202411363093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-05-02
AI Technical Summary
LLZO solid electrolyte materials are prone to react with moisture and carbon dioxide in the air during nanoification, resulting in a decrease in lithium ion conductivity and degradation of battery performance.
A lithium silicate layer is provided on the surface of the nano-formed oxide solid electrolyte particles to inhibit the detachment of lithium and the formation of surface alkali, and improve the air stability of the material.
It effectively maintains the high ionic conductivity of the oxide solid electrolyte material, improves its stability in air, extends the cycle life of the battery and enhances safety performance.
Smart Images

Figure CN119920962A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of new energy technology, and specifically relates to an oxide solid electrolyte material and a preparation method thereof, a diaphragm-free lithium-ion battery, a lithium-ion battery, and electrical equipment. Background Art
[0002] Separator-free and separator-based solid-state lithium metal batteries can realize high energy storage devices because they have good compatibility with lithium metal anodes and high-voltage cathodes. Solid electrolytes have higher thermal stability than current lithium-ion battery liquid electrolytes. For example, garnet-type solid electrolyte material LLZO (Li7La3Zr2O 12 ) has 1mS cm -1 The high room-temperature ionic conductivity, high electrochemical stability, and wide voltage window make it one of the most promising candidates for commercial applications.
[0003] As is known to all, LLZO easily reacts with trace amounts of water and carbon dioxide in the atmosphere. This causes the Li in the lattice to exchange with H to form protonated LLZO (H x Li 7-x La3Zr2O 12 ), lithium hydroxide and carbonate surface layer (hereinafter referred to as surface layer). The resulting heterogeneous surface layer has very low lithium ion conductivity, thus increasing the interface resistance between LLZO and the positive and negative electrodes, which on the one hand leads to a decrease in battery performance, and on the other hand, it is easy to cause uneven current distribution at the negative electrode interface, nucleation of lithium metal dendrites and cause battery short circuit. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the purpose of the present application is to propose an oxide solid electrolyte material and a preparation method thereof, a diaphragm-free lithium-ion battery, a lithium-ion battery, and an electrical device. The present application provides a lithium silicate layer on the surface of nano-sized oxide solid electrolyte particles. On the one hand, it can effectively inhibit the release of internal lithium in the solid electrolyte during the nano-sizing process to form a surface alkali. On the other hand, it can also convert the original surface alkali into a lithium silicate protective layer, effectively improving its stability in the air, and can effectively inhibit the continuous side reactions of the oxide solid electrolyte with moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a high ionic conductivity.
[0005] In one aspect of the present application, the present application proposes an oxide solid electrolyte material. According to an embodiment of the present application, the oxide solid electrolyte material includes:
[0006] Oxide solid electrolyte particles, wherein the particle size of the oxide solid electrolyte particles is at the nanometer level, the surface layer of the oxide solid electrolyte particles is a lithium silicate layer, and the lithium silicate layer includes lithium silicate.
[0007] According to the oxide solid electrolyte material of the embodiment of the present application, by providing a lithium silicate layer on the surface of the nano-sized oxide solid electrolyte particles, on the one hand, it can effectively inhibit the release of internal lithium in the solid electrolyte during the nano-sizing process to form a surface alkali, and on the other hand, it can also convert the original surface alkali into a lithium silicate protective layer, effectively improving its stability in the air, and can effectively inhibit the continuous side reactions of the oxide solid electrolyte with moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a relatively high ionic conductivity.
[0008] In addition, the oxide solid electrolyte material according to the above embodiment of the present application may also have the following additional technical features:
[0009] In some embodiments of the present application, the oxide solid electrolyte particles include at least one of lithium lanthanum zirconium oxide solid electrolyte particles and lithium lanthanum titanium oxide solid electrolyte particles.
[0010] In some embodiments of the present application, the lithium lanthanum zirconium oxygen solid electrolyte particles are garnet-type cubic phase lithium lanthanum zirconium oxygen solid electrolyte particles.
[0011] In some embodiments of the present application, the particle size of the oxide solid electrolyte particles is 50nm-1000nm; and / or the mass content of the lithium silicate in the oxide solid electrolyte material is 0.1%-5%; and / or the thickness of the lithium silicate layer is 3nm-50nm.
[0012] In some embodiments of the present application, the particle size of the oxide solid electrolyte particles is 200 nm to 800 nm.
[0013] In a second aspect of the present application, the present application proposes a method for preparing the above-mentioned oxide solid electrolyte material. According to an embodiment of the present application, the method comprises:
[0014] Mixing an initial oxide solid electrolyte material, a first moisture absorbent and a solvent, and grinding to obtain a nano-mixed slurry, wherein the first moisture absorbent includes at least one of silicates;
[0015] Drying the nano-mixed slurry to obtain nano-powder;
[0016] The nano powder and lithium hydroxide are mixed and reacted at high temperature to obtain an oxide solid electrolyte material.
[0017] According to the method for preparing the above-mentioned oxide solid electrolyte material in the embodiment of the present application, by adding the first hygroscopic agent during the nano-process of the oxide solid electrolyte material, on the one hand, the solid electrolyte can be effectively inhibited from releasing internal lithium during the nano-process to form a surface alkali, and on the other hand, the original surface alkali can be converted into a lithium silicate protective layer, which effectively improves its stability in the air, and can effectively inhibit the oxide solid electrolyte from continuously reacting with moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a high ionic conductivity. At the same time, the preparation process is simple, the preparation efficiency is significantly improved, and it is very suitable for large-scale production and application. In addition, the raw materials used in this application are cheap and have a high yield, and the preparation method is suitable for large-scale industrial production.
[0018] In addition, the method for preparing the above-mentioned oxide solid electrolyte material according to the above-mentioned embodiment of the present application may also have the following additional technical features:
[0019] In some embodiments of the present application, the first desiccant includes at least one of sodium silicate, potassium silicate, aluminum silicate, lithium silicate and calcium silicate; and / or the particle size of the first desiccant is 20 nm to 950 nm.
[0020] In some embodiments of the present application, based on the mass of the initial oxide solid electrolyte material being 100%, the mass of the first moisture absorbent is 0.1% to 3%.
[0021] In some embodiments of the present application, an initial oxide solid electrolyte material, a first desiccant, a second desiccant and a solvent are mixed and ground to obtain a nano-mixed slurry, wherein the second desiccant includes at least one of calcium chloride, lithium chloride and silicon dioxide.
[0022] In some embodiments of the present application, based on the mass of the initial oxide solid electrolyte material being 100%, the mass of the second desiccant is 0.1% to 2%; and / or the particle size of the second desiccant is 20nm to 950nm.
[0023] In some embodiments of the present application, the molar ratio of the first hygroscopic agent to the lithium hydroxide is 1:(1-2).
[0024] In some embodiments of the present application, the temperature of the high temperature reaction is 400° C. to 600° C., and the time is 3 h to 18 h.
[0025] In the third aspect of the present application, the present application proposes a solid electrolyte. According to an embodiment of the present application, the solid electrolyte comprises the oxide solid electrolyte material described in the above embodiment or comprises the oxide solid electrolyte material obtained by the method described in the above embodiment. The solid electrolyte has good chemical stability and high ionic conductivity.
[0026] In the fourth aspect of the present application, the present application proposes a diaphragm-free lithium-ion battery. According to an embodiment of the present application, the above-mentioned diaphragm-free lithium-ion battery includes the solid electrolyte described in the above embodiment. As a result, the safety performance, energy density, cycle life, charge and discharge rate and environmental adaptability of the diaphragm-free lithium-ion battery can be effectively improved.
[0027] In the fifth aspect of the present application, the present application proposes a lithium-ion battery. According to an embodiment of the present application, the above lithium-ion battery includes the solid electrolyte described in the above embodiment. Thus, the safety performance, energy density, cycle life, charge and discharge rate and environmental adaptability of the lithium-ion battery can be effectively improved.
[0028] In the sixth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has the lithium-ion battery or the diaphragm-free lithium-ion battery described in the above embodiment. Therefore, the electric device has all the advantages of the battery, which will not be repeated here.
[0029] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0031] Figure 1 This is a schematic diagram of the process of preparing oxide solid electrolyte materials according to some embodiments of the present application. DETAILED DESCRIPTION
[0032] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.
[0033] In one aspect of the present application, the present application proposes an oxide solid electrolyte material. According to an embodiment of the present application, the oxide solid electrolyte material includes: oxide solid electrolyte particles, the particle size of the oxide solid electrolyte particles is nanometer level, the surface layer of the oxide solid electrolyte particles is a lithium silicate layer, and the lithium silicate layer includes lithium silicate.
[0034] The beneficial effects that can be achieved by the oxide solid electrolyte material proposed in this application are described in detail below:
[0035] In the related art, the oxide solid electrolyte material will lead to an increase in specific surface area and the generation of a large number of fresh surfaces during the nano-sizing process. The fresh surface easily reacts with moisture and carbon dioxide in the air to generate an alkaline surface layer (mainly lithium hydroxide and lithium carbonate). On the one hand, the generation of the surface layer will consume the internal lithium of the solid electrolyte, resulting in a significant decrease in its ionic conductivity; on the other hand, the alkaline surface layer mainly includes lithium hydroxide and lithium carbonate, which leads to a significant increase in the surface impedance of the oxide solid electrolyte material, which is not conducive to its application. In addition, since the lithium hydroxide contained in the surface layer is strongly alkaline, it will seriously affect its application.
[0036] In view of this, the present application sets a lithium silicate layer on the surface of nano-sized oxide solid electrolyte particles, which can effectively inhibit the release of internal lithium in the solid electrolyte during the nano-sizing process to form a surface alkali, and on the other hand, it can also convert the original surface alkali into a lithium silicate protective layer, effectively improving its stability in the air, and can effectively inhibit the continuous side reactions of the oxide solid electrolyte with moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a high ionic conductivity. At the same time, it can also stabilize the cubic phase structure of the oxide solid electrolyte, especially the cubic phase structure of the lithium lanthanum zirconium oxygen solid electrolyte.
[0037] According to some specific embodiments of the present application, the oxide solid electrolyte particles include at least one of lithium lanthanum zirconium oxide solid electrolyte particles and lithium lanthanum titanium oxide solid electrolyte particles. That is to say, the technical concept of the present application is not only applicable to lithium lanthanum zirconium oxide solid electrolytes (LLZO, Li7La3Zr2O 12 ), also suitable for lithium lanthanum titanium oxide solid electrolyte (LLTO, Li 0.33 La 0.56 TiO3), which can effectively inhibit the release of internal lithium in the above-mentioned oxide solid electrolyte during the nano-scaling process to form a surface alkali. On the other hand, it can also convert the original surface alkali of the above-mentioned oxide solid electrolyte into a lithium silicate protective layer, effectively improving its stability in the air, and can effectively inhibit the above-mentioned oxide solid electrolyte from continuously reacting with moisture and carbon dioxide in the air.
[0038] According to some further specific embodiments of the present application, the lithium lanthanum zirconium oxygen solid electrolyte particles are garnet-type cubic phase lithium lanthanum zirconium oxygen solid electrolytes. Therefore, the garnet-type cubic phase lithium lanthanum zirconium oxygen solid electrolyte has excellent electrical conductivity.
[0039] In an embodiment of the present application, metal elements such as tantalum (Ta), aluminum (Al), niobium (Nb), gallium (Bi), etc. can be doped into the oxide solid electrolyte material to optimize its structure and performance, improve ionic conductivity and reduce interface resistance.
[0040] According to some specific embodiments of the present application, the mass content of lithium hydroxide in the lithium silicate layer is not more than 0.3%, and the mass content of lithium carbonate in the lithium silicate layer is not more than 1%. However, the mass content of lithium hydroxide in the alkaline surface layer of the existing oxide solid electrolyte is about 3%, and the mass content of lithium carbonate is about 5%.
[0041] According to some specific embodiments of the present application, the particle size of the above-mentioned nano-scale oxide solid electrolyte particles is 50nm to 1000nm, for example, it can be 50nm, 100nm, 200nm, 3000nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, etc. By limiting the particle size of the oxide solid electrolyte particles within the above range, the nano-step of the oxide solid electrolyte material is avoided, thereby avoiding the oxide solid electrolyte material from producing a fresh surface during the nano-process. The fresh surface is easy to react with moisture and carbon dioxide in the air to generate an alkaline surface layer (mainly lithium hydroxide and lithium carbonate). On the one hand, the generation of the alkaline surface layer will consume the internal lithium of the solid electrolyte, resulting in a significant decrease in its ionic conductivity. On the other hand, because the lithium hydroxide contained in the surface layer has strong alkalinity, it will seriously affect its application. Preferably, the particle size of the oxide solid electrolyte particles is 200nm to 800nm.
[0042] According to some specific embodiments of the present application, the mass content of lithium silicate in the oxide solid electrolyte material is 0.1%-5%, for example, it can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, etc. Thus, the stability of the oxide solid electrolyte material in the air can be further improved, and the continuous side reaction between the oxide solid electrolyte and moisture and carbon dioxide in the air can be further effectively suppressed.
[0043] According to some specific embodiments of the present application, the thickness of the lithium silicate layer is 3nm-50nm, for example, 3nm, 5nm, 10nm, 20nm, 30nm, 40nm, 50nm, etc. Thus, the stability of the oxide solid electrolyte material in the air can be further improved, and the continuous side reaction between the oxide solid electrolyte and moisture and carbon dioxide in the air can be further effectively suppressed.
[0044] In the second aspect of the present application, the present application proposes a method for preparing the above oxide solid electrolyte material. Figure 1 The method comprises: mixing an initial oxide solid electrolyte material, a first desiccant and a solvent, grinding to obtain a nano-mixed slurry, wherein the first desiccant comprises at least one of silicates; drying the nano-mixed slurry to obtain a nano-powder; mixing the nano-powder and lithium hydroxide, reacting at a high temperature to obtain an oxide solid electrolyte material.
[0045] The beneficial effects that can be achieved by the method for preparing the above-mentioned oxide solid electrolyte material proposed in this application are described in detail below:
[0046] In the related art, the oxide solid electrolyte material will lead to an increase in specific surface area and the generation of a large number of fresh surfaces during the nano-sizing process. The fresh surface easily reacts with moisture and carbon dioxide in the air to generate an alkaline surface layer (mainly lithium hydroxide and lithium carbonate). On the one hand, the generation of the surface layer will consume the internal lithium of the solid electrolyte, resulting in a significant decrease in its ionic conductivity; on the other hand, the alkaline surface layer mainly includes lithium hydroxide and lithium carbonate, which leads to a significant increase in the surface impedance of the oxide solid electrolyte material, which is not conducive to its application. In addition, since the lithium hydroxide contained in the surface layer is strongly alkaline, it will seriously affect its application.
[0047] In addition, the solid-phase sintering process for preparing lithium oxide solid electrolytes requires a large amount of excess lithium salt, which will result in a large amount of lithium oxide remaining on the surface of the oxide solid electrolyte. If it comes into contact with air, it will easily form lithium carbonate or lithium hydroxide, which will significantly increase the surface impedance of the oxide solid electrolyte, which is not conducive to its application.
[0048] In view of this, the present application provides a novel method for preparing a nano-sized solid electrolyte. By adding a first hygroscopic agent during the nano-sized process of an oxide solid electrolyte material, on the one hand, the solid electrolyte can be effectively inhibited from releasing internal lithium during the nano-sized process to form a surface base. On the other hand, the original surface base can be converted into a lithium silicate protective layer, which effectively improves its stability in the air, and can effectively inhibit the oxide solid electrolyte from continuously reacting with moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a high ionic conductivity. Specifically, the first hygroscopic agent includes at least one of silicates, which easily reacts with moisture and carbon dioxide on the surface of the initial oxide solid electrolyte material to generate silicic acid and carbonate, and silicic acid can react with the original surface base to generate lithium silicate coated on the surface of the material, thereby utilizing the first hygroscopic agent to absorb water easily to effectively reduce the occurrence of side reactions on the surface of the oxide solid electrolyte, and greatly improve stability in the air. At the same time, the preparation process is simple, the preparation efficiency is significantly improved, and the stability of the oxide solid electrolyte material in the air is also significantly improved, which is very suitable for large-scale production and application. In addition, the raw materials used in the present application are cheap and have a high yield, and the preparation method is suitable for large-scale industrial production.
[0049] Na2SiO3+CO2+H2O=H2SiO3+Na2CO3 (1)
[0050] H2SiO3+2LiOH=Li2SiO3+2H2O (2)
[0051] Specifically, refer to the attached Figure 1 , the above preparation method comprises the following steps:
[0052] S100: mixing and grinding an initial oxide solid electrolyte material, a first moisture absorbent and a solvent to obtain a nano-mixed slurry;
[0053] In this step, the initial oxide solid electrolyte material, the first moisture absorber and the solvent are mixed and ground at high speed to obtain a nano-mixed slurry, wherein the first moisture absorber includes at least one of silicates. Thus, in this step, the first moisture absorber silicate easily reacts with the moisture and carbon dioxide on the surface of the initial oxide solid electrolyte material to generate silicic acid and carbonate, as shown in the chemical reaction equation (1). The purpose of grinding is to nano-size the initial oxide solid electrolyte material to obtain a nano-scale oxide solid electrolyte material.
[0054] In the embodiments of the present application, the time of the high-speed grinding is not particularly limited. As some specific embodiments, the high-speed grinding is performed for 0.5 h to 6 h to form a uniform nano-slurry.
[0055] In the embodiments of the present application, the specific type of the above-mentioned first desiccant is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred embodiments, the first desiccant includes at least one of sodium silicate, potassium silicate, aluminum silicate, lithium silicate and calcium silicate. The above-mentioned types of silicates can react with moisture and carbon dioxide on the surface of the initial oxide solid electrolyte material to generate silicic acid and carbonate.
[0056] According to some specific embodiments of the present application, the particle size of the first desiccant is 20nm to 950nm, and is smaller than the particle size of the oxide solid electrolyte particles, for example, it can be 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, etc. Thus, it is beneficial to disperse the first desiccant in the oxide solid electrolyte material, and it is also beneficial for the first desiccant to fully react with the moisture and carbon dioxide on the surface of the initial oxide solid electrolyte material.
[0057] According to some further specific embodiments of the present application, based on the mass of the initial oxide solid electrolyte material being 100%, the mass of the first desiccant is 0.1% to 3%, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, etc. By limiting the amount of the first desiccant to the above range, it can be further ensured that the first desiccant fully reacts with the moisture and carbon dioxide on the surface of the initial oxide solid electrolyte material.
[0058] According to some specific embodiments of the present application, the initial oxide solid electrolyte material, the first moisture absorber, the second moisture absorber and the solvent are mixed and ground to obtain a nano-mixed slurry, and the second moisture absorber includes at least one of calcium chloride, lithium chloride and silicon dioxide. The purpose of the second moisture absorber is to further absorb moisture on the surface of the initial oxide solid electrolyte material, further reduce the occurrence of side reactions on the surface of the oxide solid electrolyte, and thus greatly improve the stability of the oxide solid electrolyte in the air.
[0059] According to some further specific embodiments of the present application, based on the mass of the initial oxide solid electrolyte material being 100%, the mass of the second desiccant is 0.1% to 2%, for example, it can be 0.1%, 0.5%, 1%, 1.5%, 2%, etc. By limiting the amount of the second desiccant to the above range, the occurrence of side reactions on the surface of the oxide solid electrolyte can be further reduced, thereby greatly improving the stability of the oxide solid electrolyte in the air.
[0060] According to some other specific embodiments of the present application, the particle size of the second desiccant is 20nm to 950nm, and is smaller than the particle size of the oxide solid electrolyte particles, for example, it can be 20nm, 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, etc. Thus, it is beneficial to disperse the second desiccant in the oxide solid electrolyte material, and it is also beneficial for the second desiccant to fully absorb the moisture on the surface of the initial oxide solid electrolyte material.
[0061] In the embodiments of the present application, the purpose of the above-mentioned solvent is to disperse the initial oxide solid electrolyte material, the first desiccant and the optional second desiccant, and the specific type thereof is not particularly limited. For example, an alcohol solvent can be used. As a specific example, at least one of ethanol and isopropanol can be used.
[0062] In the embodiments of the present application, the preparation method of the above-mentioned initial oxide solid electrolyte material is not particularly limited. As some specific embodiments, the preparation method of the above-mentioned initial oxide solid electrolyte material includes:
[0063] Solid phase sintering method: raw materials lithium source (such as lithium carbonate Li2CO3, can be 15% excess), lanthanum source (such as lanthanum oxide La2O3), zirconium source (such as zirconium oxide ZrO2) and optional tantalum source (such as tantalum pentoxide) are sintered according to Li 6.5 Ln3Z 1.5 Ta 0.5 O 12The mixture is mixed in a ratio of 200 μm to 400 μm and then sintered at a high temperature to prepare LLZTO. The sintered product is then crushed and sieved to obtain LLZTO powder (if no tantalum source is used, LLZO is prepared), and the powder particle size D50 is 5 μm to 15 μm.
[0064] In an embodiment of the present application, metal elements such as tantalum (Ta), aluminum (Al), niobium (Nb), gallium (Bi), etc. can be doped during the preparation of the initial oxide solid electrolyte material to optimize its structure and performance, improve ionic conductivity and reduce interface resistance.
[0065] S200: drying the nano-mixed slurry to obtain nano-powder;
[0066] In this step, the nano-mixed slurry can be dried by centrifugation or vacuum drying to remove the solvent in the nano-mixed slurry to obtain nano-powder, which includes silicic acid.
[0067] S300: Mix the nano powder and lithium hydroxide and react at high temperature to obtain an oxide solid electrolyte material.
[0068] In this step, nano powder (the nano powder includes the silicic acid obtained in step S100) and lithium hydroxide are mixed.
[0069] At high temperature, the silicate in the nanopowder reacts with the lithium hydroxide / lithium oxide on the surface of the nanosized oxide solid electrolyte particles and the newly added lithium hydroxide in this step to generate lithium silicate coated on the surface of the material, as shown in the chemical reaction equation (2), thereby effectively improving the stability of the oxide solid electrolyte material in the air and effectively inhibiting the continuous side reaction between the oxide solid electrolyte and moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a high ionic conductivity.
[0070] According to some other specific embodiments of the present application, the temperature of the high-temperature reaction is 400°C to 600°C (for example, it can be 400°C, 450°C, 500°C, 550°C, 600°C, etc.), and the time is 3h to 18h (for example, it can be 3h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, etc.). By limiting the temperature and time of the high-temperature reaction within the above range, it can be further ensured that the silicic acid in the nanopowder fully reacts with the lithium hydroxide / lithium oxide on the surface of the nanosized oxide solid electrolyte particles and the newly added lithium hydroxide in this step to generate lithium silicate coated on the surface of the material.
[0071] According to some other specific embodiments of the present application, the molar ratio of the first desiccant to lithium hydroxide is 1:(1-2), for example, it can be 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6, 1:1.8, 1:2, etc. By limiting the molar ratio of the first desiccant to lithium hydroxide within the above range, it can be further ensured that the silicic acid in the nanopowder fully reacts with the lithium hydroxide / lithium oxide on the surface of the nanosized oxide solid electrolyte particles and the newly added lithium hydroxide in this step to generate lithium silicate coated on the surface of the material.
[0072] Furthermore, the above preparation method also includes:
[0073] Tableting: Weigh a certain amount of the oxide solid electrolyte powder prepared in step S300, add the pre-prepared polyvinyl alcohol binder to the oxide solid electrolyte powder according to a certain mass ratio, and the mass of the polyvinyl alcohol binder is 20% to 30% of the oxide solid electrolyte powder. Grind in a mortar to mix the powder and the PVA solution evenly. Dry, and after drying is complete, put the powder in a mold and keep it at a pressure of 150MPa to 250MPa for 5min to 15min to obtain a formed disc with a diameter of 15mm to 20mm.
[0074] The pressed pieces are then placed in an oven at 40°C to 60°C to remove the solvent in the binder. The pieces are then placed upright in an open crucible and heated to 400°C to 500°C in a muffle furnace at a heating rate of 1°C / min to 5°C / min and kept at that temperature for 3h to 5h for debinding.
[0075] Finally, the ceramic piece after debinding is double-sided polished, coated with a layer of silver paste and dried, and then EIS test is carried out.
[0076] In the third aspect of the present application, the present application proposes a solid electrolyte. According to an embodiment of the present application, the solid electrolyte comprises the oxide solid electrolyte material described in the above embodiment or comprises the oxide solid electrolyte material obtained by the method described in the above embodiment. The solid electrolyte has good chemical stability and high ionic conductivity.
[0077] In the fourth aspect of the present application, the present application proposes a diaphragm-free lithium-ion battery. According to an embodiment of the present application, the above-mentioned diaphragm-free lithium-ion battery includes the solid electrolyte described in the above embodiment. As a result, the safety performance, energy density, cycle life, charge and discharge rate and environmental adaptability of the diaphragm-free lithium-ion battery can be effectively improved.
[0078] In the fifth aspect of the present application, the present application proposes a lithium-ion battery. According to an embodiment of the present application, the above lithium-ion battery includes the solid electrolyte described in the above embodiment. Thus, the safety performance, energy density, cycle life, charge and discharge rate and environmental adaptability of the lithium-ion battery can be effectively improved.
[0079] The membrane-free lithium-ion battery or lithium-ion battery of the present application may include a battery cell form, a battery module form and a battery pack form. In some embodiments, the battery cells can be assembled into a battery module, and the number of battery cells contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module. In some embodiments, the battery module can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery pack.
[0080] In the sixth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device has the lithium-ion battery or the diaphragm-free lithium-ion battery described in the above embodiment. Therefore, the electric device has all the advantages of the battery, which will not be repeated here.
[0081] Specifically, the electrical equipment may be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.
[0082] The embodiments of the present application are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. In addition, unless otherwise explicitly stated, all reagents used in the following embodiments are commercially available or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0083] Example 1
[0084] This embodiment provides an oxide solid electrolyte material, and the preparation method thereof includes:
[0085] (1) First, the raw materials lithium carbonate, lanthanum oxide, and zirconium oxide are respectively subjected to air flow pulverization, wherein the lanthanum oxide is placed in a muffle furnace for calcination at 900° C. for 8 hours, and the lithium carbonate and zirconium oxide are placed in an oven at 120° C. for drying for 12 hours. After calcination and drying, they are vacuum packaged for standby use.
[0086] (2) According to the molar ratio of Li:La:Zr:Ta of 6.5:3:1.5:0.5, 59.96g lithium carbonate (10% excess), 110.93g lanthanum oxide, 41.95g zirconium oxide and 26.77g tantalum oxide were weighed and put into a ball mill. Large zirconium balls (8mm in diameter), medium balls (5mm in diameter) and small balls (2mm in diameter) were mixed into mixed zirconium balls in a mass ratio of 1:2:3. According to the mass ratio of balls and materials of about 1:1, 240g mixed zirconium oxide balls were weighed and put into a ball mill. The ball mill speed was set to 500r / min, forward rotation for 30min, interval for 30min, reverse rotation for 30min, ball mill for 24h, take out and sieve to obtain the mixed material. The mixture is loaded into a crucible and placed in a muffle furnace, first heated to 950°C for pre-sintering for 6 hours, then heated to 1175°C for further sintering for 6 hours, and then crushed and sieved to obtain initial lithium lanthanum zirconium oxide powder with a particle size of 5μm to 20μm.
[0087] (3) Modification of initial lithium lanthanum zirconium oxide powder:
[0088] 3-1) The initial lithium lanthanum zirconium oxide powder is mixed with the first hygroscopic sodium silicate powder (particle size is 20nm ~ 400nm) and the solvent ethanol, and high-speed grinding is performed for 4h to form a uniform nano-slurry, wherein the mass of the sodium silicate powder is 1% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0089] 3-2) The obtained slurry is centrifuged and dried under vacuum at 120° C. to obtain nanopowder.
[0090] 3-3) The above-mentioned nanopowder is fully mixed with an appropriate amount of lithium hydroxide powder, wherein the molar ratio of sodium silicate powder to lithium hydroxide powder is 1:2, and the obtained mixed powder is heat-treated at 500°C for 10 hours, and then sieved to obtain lithium lanthanum zirconium oxygen solid electrolyte powder with a particle size of 200nm to 800nm. According to the test, the mass content of lithium silicate in the oxide solid electrolyte powder is about 1%, and the thickness of the lithium silicate layer is about 10nm.
[0091] 3-4) Tableting: Weigh 2g of the lithium lanthanum zirconium oxide solid electrolyte powder obtained in step 3-3) above, add the pre-prepared binder PVA solution (the mass percentage concentration of the PVA solution is 10%) to the lithium lanthanum zirconium oxide solid electrolyte powder, wherein the mass of the PVA solution is 25% of the mass of the lithium lanthanum zirconium oxide solid electrolyte powder. Grind in an agate mortar to mix the lithium lanthanum zirconium oxide solid electrolyte powder and the PVA solution evenly. Dry, and after it is completely dried, place the powder in a mold under a pressure of 200MPa for 10 minutes to obtain a formed disc with a diameter of 17mm.
[0092] 3-5) The formed sheet pressed in step 3-4) is placed in an oven at 50°C to dry out the deionized water in the binder. The formed sheet is then placed upright in an open crucible and heated to 450°C in a muffle furnace at a heating rate of 2°C / min for 4 hours for debinding.
[0093] 3-6) The ceramic sheet after debinding is double-sided polished, coated with a layer of silver paste and dried, and then subjected to EIS test.
[0094] Example 2
[0095] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0096] 3-1) The mass of the first moisture absorbent sodium silicate powder is 0.3% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0097] According to tests, the mass content of lithium silicate in the oxide solid electrolyte powder is about 0.3%, and the thickness of the lithium silicate layer is about 3 nm.
[0098] Example 3
[0099] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0100] 3-1) The mass of the first moisture absorbent sodium silicate powder is 2% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0101] According to tests, the mass content of lithium silicate in the oxide solid electrolyte powder is about 2%, and the thickness of the lithium silicate layer is about 20 nm.
[0102] Example 4
[0103] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0104] 3-1) The mass of the first moisture absorbent sodium silicate powder is 3% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0105] Example 5
[0106] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0107] 3-3) The molar ratio of the first moisture absorbent sodium silicate powder to the lithium hydroxide powder is 1:1.8.
[0108] Example 6
[0109] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0110] 3-3) The molar ratio of the first moisture absorbent sodium silicate powder to the lithium hydroxide powder is 1:1.5.
[0111] Example 7
[0112] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0113] 3-3) The molar ratio of the first moisture absorbent sodium silicate powder to the lithium hydroxide powder is 1:1.2.
[0114] Example 8
[0115] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0116] 3-1) The first moisture absorbent sodium silicate powder is replaced with aluminum silicate powder.
[0117] Example 9
[0118] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0119] 3-1) The first moisture absorbent sodium silicate powder is replaced with lithium silicate powder.
[0120] Example 10
[0121] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0122] 3-1) The first moisture absorbent sodium silicate powder is replaced with calcium silicate powder.
[0123] Embodiment 11
[0124] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0125] 3-3) The above nanopowder is fully mixed with an appropriate amount of lithium hydroxide powder, and the resulting mixed powder is heat treated at 400° C. for 18 hours.
[0126] Example 12
[0127] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0128] 3-3) The above nanopowder is fully mixed with an appropriate amount of lithium hydroxide powder, and the resulting mixed powder is heat treated at 600° C. for 3 h.
[0129] Embodiment 13
[0130] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0131] 3-1) The initial lithium lanthanum zirconium oxide powder is mixed with the first hygroscopic agent sodium silicate powder (particle size is 20nm ~ 400nm), the second hygroscopic agent calcium chloride (particle size is 20nm ~ 400nm), and the solvent ethanol, and high-speed grinding is performed for 4h to form a uniform nano-slurry, wherein the mass of the second hygroscopic agent calcium chloride is 0.1% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0132] Embodiment 14
[0133] The preparation methods of this embodiment are basically the same as those of embodiment 13, except that:
[0134] 3-1) The mass of the second moisture absorbent calcium chloride is 1% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0135] Embodiment 15
[0136] The preparation methods of this embodiment are basically the same as those of embodiment 13, except that:
[0137] 3-1) The mass of the second moisture absorbent calcium chloride is 2% of the mass of the initial lithium lanthanum zirconium oxide powder.
[0138] Example 16
[0139] The preparation methods of this embodiment are basically the same as those of embodiment 14, except that:
[0140] 3-1) The second moisture absorbent calcium chloride is replaced by lithium chloride.
[0141] Embodiment 17
[0142] The preparation methods of this embodiment are basically the same as those of embodiment 14, except that:
[0143] 3-1) The second moisture absorbent calcium chloride is replaced by silicon dioxide.
[0144] Embodiment 18
[0145] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:
[0146] (1) The raw material zirconium oxide in Example 1 was replaced with titanium dioxide, and the raw materials were mixed in a ratio of Li:La:Ti of 0.33:0.56:1.0;
[0147] (2) The sintering temperature is 1250℃ and the sintering time is 6h.
[0148] Comparative Example 1
[0149] The difference between this comparative example and Example 1 is:
[0150] The initial lithium lanthanum zirconium oxide powder having a particle size of 5 μm to 20 μm was prepared by the same method as in Example 1, but the initial lithium lanthanum zirconium oxide powder was not modified.
[0151] The impedance value, initial lithium ion conductivity and lithium ion conductivity after being placed in the air for 30 days of the products obtained in Examples 1 to 18 and Comparative Example 1 were tested respectively, and the test methods were as follows, and the results were shown in Table 1. The alkali content of the surface layer (i.e., lithium silicate layer) of the oxide solid electrolyte particles obtained in Examples 1 to 18 and Comparative Example 1 was tested respectively, and the test methods were as follows, and the results were shown in Table 1.
[0152] Impedance value test:
[0153] The impedance values of the ceramic sheet samples for testing in the above embodiments and comparative examples were measured by AC impedance testing methods. Specifically, the test samples were placed in a Chenhua electrochemical workstation to test AC impedance, with the frequency set to 0.1-1 MHZ and the voltage amplitude set to 5 mV. The test results are shown in Table 1.
[0154] Initial lithium ion conductivity test:
[0155] The lithium ion conductivity of the ceramic sheet samples used in the test of the embodiment and the comparative example is obtained by the following formula:
[0156] Ionic conductivity σ = h / RA;
[0157] Where: h-sample thickness (cm);
[0158] R-sample impedance (Ω);
[0159] A-Circular cross-sectional area of sample (cm 2 ).
[0160] The impedance values and lithium ion conductivity of the lithium lanthanum zirconium oxide ceramic sheets obtained in the embodiment and the comparative example were calculated by a fitting method, and the fitting software used was Zview 2. The results are shown in Table 1.
[0161] Lithium ion conductivity test after 30 days in air:
[0162] The ceramic sheet samples for testing of the embodiment and the comparative example were placed in air for 30 days and then tested for lithium ion conductivity. The test method was consistent with the above test method. The results are shown in Table 1.
[0163] Alkali content test of the surface layer (i.e. lithium silicate layer):
[0164] A certain amount of lithium lanthanum zirconium oxide powder obtained in the example and the comparative example was stirred in deionized water, and the filtrate was filtered and then subjected to potentiometric titration to determine the contents of lithium hydroxide and lithium carbonate therein.
[0165] Table 1
[0166]
[0167]
[0168] It can be seen from Table 1 that, compared with Comparative Example 1, the alkali content of Examples 1 to 18 is significantly reduced, the impedance values of Examples 1 to 18 are significantly reduced, and the initial lithium ion conductivity of Examples 1 to 18 and the lithium ion conductivity after being placed in the air for 30 days are significantly improved. It can be seen that by adding the first desiccant during the nano-sizing process of the oxide solid electrolyte material, the original surface alkali can be converted into a lithium silicate protective layer, which effectively improves its stability in the air, and can effectively inhibit the continuous side reactions of the oxide solid electrolyte with moisture and carbon dioxide in the air, so that the oxide solid electrolyte material can maintain a relatively high ionic conductivity.
[0169] It can also be seen from Table 1 that, compared with Example 1, the surface alkali content of Examples 13 to 17 is further reduced, the impedance values of Examples 13 to 17 are increased, and the initial lithium ion conductivity and the lithium ion conductivity after being placed in the air for 30 days are reduced. It can be seen that by further adding the second desiccant during the nano-sizing process of the oxide solid electrolyte material, the occurrence of side reactions on the surface of the oxide solid electrolyte can be further reduced, thereby further improving the stability of the oxide solid electrolyte in the air and further reducing the surface alkali content. However, the second desiccant cannot form a good fast ion conductor on the electrolyte surface, and therefore will affect the ionic conductivity of the oxide solid electrolyte material.
[0170] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0171] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. An oxide solid electrolyte material, characterized in that: include: Oxide solid electrolyte particles, wherein the particle size of the oxide solid electrolyte particles is at the nanometer level, the surface layer of the oxide solid electrolyte particles is a lithium silicate layer, and the lithium silicate layer includes lithium silicate.
2. The oxide solid electrolyte material according to claim 1, characterized in that The oxide solid electrolyte particles include at least one of lithium lanthanum zirconium oxide solid electrolyte particles and lithium lanthanum titanium oxide solid electrolyte particles.
3. The oxide solid electrolyte material according to claim 2, characterized in that: The lithium lanthanum zirconium oxygen solid electrolyte particles are garnet-type cubic phase lithium lanthanum zirconium oxygen solid electrolyte particles.
4. The oxide solid electrolyte material according to claim 1, characterized in that The particle size of the oxide solid electrolyte particles is 50nm to 1000nm; And / or, the mass content of the lithium silicate in the oxide solid electrolyte material is 0.1%-5%; And / or, the thickness of the lithium silicate layer is 3nm-50nm.
5. The oxide solid electrolyte material according to claim 1, characterized in that: The particle size of the oxide solid electrolyte particles is 200nm to 800nm.
6. A method for preparing the oxide solid electrolyte material according to any one of claims 1 to 5, characterized in that: include: Mixing an initial oxide solid electrolyte material, a first moisture absorbent and a solvent, and grinding to obtain a nano-mixed slurry, wherein the first moisture absorbent includes at least one of silicates; Drying the nano-mixed slurry to obtain nano-powder; The nano powder and lithium hydroxide are mixed and reacted at high temperature to obtain an oxide solid electrolyte material.
7. The method according to claim 6, characterized in that The first moisture absorbent includes at least one of sodium silicate, potassium silicate, aluminum silicate, lithium silicate and calcium silicate; And / or, the particle size of the first moisture absorbent is 20nm to 950nm.
8. The method according to claim 6, characterized in that Based on 100% of the mass of the initial oxide solid electrolyte material, the mass of the first moisture absorbent is 0.1% to 3%.
9. The method according to claim 6, characterized in that The initial oxide solid electrolyte material, the first moisture absorber, the second moisture absorber and the solvent are mixed and ground to obtain a nano-mixed slurry, wherein the second moisture absorber includes at least one of calcium chloride, lithium chloride and silicon dioxide.
10. The method according to claim 9, characterized in that Based on the mass of the initial oxide solid electrolyte material being 100%, the mass of the second moisture absorbent is 0.1% to 2%; And / or, the particle size of the second moisture absorbent is 20 nm to 950 nm.
11. The method according to any one of claims 6 to 10, characterized in that: The molar ratio of the first moisture absorbent to the lithium hydroxide is 1:(1-2).
12. The method according to any one of claims 6 to 10, characterized in that: The temperature of the high temperature reaction is 400° C. to 600° C., and the time is 3 h to 18 h.
13. A solid electrolyte, characterized in that: include: The invention comprises the oxide solid electrolyte material according to any one of claims 1 to 5 or the oxide solid electrolyte material prepared by the method according to any one of claims 6 to 12.
14. A diaphragm-free lithium-ion battery, characterized in that: Comprising the solid electrolyte according to claim 13.
15. A lithium ion battery, characterized in that: Comprising the solid electrolyte according to claim 13.
16. An electrical equipment, characterized in that: A lithium ion battery according to claim 14 or 15.